ANALYSIS OF INFRASTRUCTURE DEVELOPMENT POLICIES IN BOTTO BENTENG VILLAGE, MAJAULENG DISTRICT, WAJO REGENCY - Eka Patmasari; Ilham (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
This study aims to analyze infrastructure development policies in Botto Benteng Village, Majauleng District, Wajo Regency. The type of research used is qualitative with a descriptive approach. Data collection was done through observation, interviews, documentation, and literature study. Data analysis was carried out through several stages; data collection, data reduction, data presentation, and conclusion drawing. The results of this research found that overall development in Bottobenteng Village has followed existing regulations. However, the implementation of village infrastructure development policies still needs to be improved. Community participation has also not been fully optimized. Regarding supervision and development, the local government has conducted monitoring. However, the supervision carried out by the community is still limited, only covering physical participation without extensive involvement from the planning stage to supervision. Supporting factors include: availability of funds, community participation, and applicable regulations. The inhibiting factors are the lack of optimal supervision from the community, weather and terrain conditions, and fluctuations in material prices. As a recommendation, it can further increase development efforts, especially in the road and bridge infrastructure sector, which is a top priority for the community in Bottobenteng Village, improve the efficiency of village development planning by involving the participation of the Botto Benteng community, and increase community supervision of the use of village government funds to ensure that no misuse of funds occurs.